Research on COVID-19 based on ARIMA modelΔ-Taking Hubei, China as an example to see the epidemic in Italy - Qiuying Yang; Jie Wang; Hongli Ma; Xihao Wang (Elsevier, 2020)
COVID-19 has spread throughout the world; various forecast models have been used to predict the development of the pandemic. The number of new cases from the outbreak to zero has gone through a complete cycle in Hubei, China, on lockdown over coronavirus. So, we created the time series ARIMA models for new cases and new deaths daily during this period. Moreover, these models have been used in Italy, which has the same population conditions and on lockdown as Hubei, in order to predict the epidemic in Italy in the next ten days and provide a theoretical basis for the development of pandemics in some countries in the future.